A Community-Based Holistic Midwifery Service Management Model To Optimize The Role Of Posyandu Cadres - Harmatuti; Dyan Oktaviany (CV. Inara, 2026)
This research on a community-based holistic midwifery service management model aims to develop and test a community-based holistic midwifery service management model to optimize the role of Posyandu (Integrated Health Post) cadres. Posyandu cadres serve as the frontline providers of community-based health services for mothers, children, adolescents, women of reproductive age, and the elderly in the community, integrating primary care (a basic health care system encompassing promotive, preventive, simple curative, and rehabilitative care) to encourage active community participation in health activities. Challenges often faced by cadres include limited health knowledge, interpersonal communication skills with the community, and coordination with health workers. The background to this research is the persistently high maternal and infant mortality rates in Indonesia and the suboptimal role of Posyandu cadres in holistic midwifery services in the community. The research method used a Research & Development (R&D) approach using the Borg & Gall model, encompassing the stages of initial research, model design, expert validation, limited trials, revisions, and field trials. The study sample consisted of 28 active Posyandu (Integrated Service Post) cadres. Data collection techniques included pre-test and post-test surveys, interviews, focus group discussions (FGDs), and field observations. Data analysis was conducted quantitatively (paired t-test, multiple regression) and qualitatively to identify, analyze, and report emerging patterns from the data in the Cisereuh District, Purwakarta Regency, in 2026.The results indicated that the implementation of a community-based holistic midwifery service management model increased the effectiveness of the role of Posyandu cadres, including increased knowledge (35.2%), improved service skills (40%), improved interpersonal communication (32.5%), and improved coordination with health workers (36.8%).The community-based holistic midwifery service management model was deemed effective in strengthening the role of Posyandu cadres, increasing community participation, and improving the quality of health services for the elderly, resulting in increased community satisfaction with Posyandu services.The conclusion of this study is that the community-based holistic midwifery management model is feasible as a strategy to strengthen primary healthcare services at the family and community levels, supporting the achievement of the SDGs (reducing maternal and infant mortality rates), and strengthening community-based health systems.